The Assessment of Human Beta Defensin-2 (Hbd-2) and Calprotectin, as Potential Biomarkers in Psoriasis - Shammar, Samar Hasan (Medical Science Journal for Advance Research, 2025)
Background: Human beta defensing 2 and calprotectin are usually not examined in relationship to one’s serum and psoriasis severity where as HBD-2 is overexpressed in the epidermis of psoriatic skin. Furthermore, calprotectin helps in sustaining physiological and pathological processes of psoriasis. Objectives: The aim of this study was to determine serum levels of Human β-defensin-2 and Calprotectin in psoriasis patients, analyze the relation to disease severity measured by the Rule of Nines, and study correlates of the studied demographic and clinical factors on such biomarkers. Methods: This study was conducted on 100 subjects (50 psoriasis patients and 50 healthy controls of matched age and gender). Psoriatic participants were further subdivided into mild, moderate, and severe groups. Serum levels of HBD-2 and Calprotectin were assessed by ELISA. Statistical tests were performed to evaluate differences between groups and levels of the measured biomarkers. Results: Markedly higher levels of HBD-2 and calprotectin were observed among the psoriasis patients in comparison to the controls (p < 0.05). Conclusion: hBD-2 and calprotectin appear to provide complementary information regarding localized skin inflammation and systemic inflammation respectively, while both skin and systemic inflammation was worsened by the condition’s activity. hBD-2 and calprotectin psoriasis biomarkers would improve disease management by allowing for the objective assessment of the disease and thus facilitate the tailoring of treatment plans.